Analysis of Learning Obstacles in Numeracy Literacy on Decimal NumberMaterial for Seventh Grade Junior High School Students in Hulu Sungai TengahRegency - Novita Konnianty Lassi; Kartika Yulianti; Eyus Sudihartinih (Universitas Pancasakti Tegal, 2026)
Numeracy literacy is a fundamental skill required by students to apply mathematical concepts in everyday life; however Indonesian students still face obstacles, particularly with decimal numbers. This research aims to analyze learning obstacles in numeracy literacy on the topic of decimal numbers. The method used is descriptive qualitative with triangulation techniques in data collection. The research result identify three interrelated categories of obstacles, namely ontogenetic obstacles in the form of limited mental readiness and prerequisite understanding, epistemological obstacles in the form of errors in decimal operations, and didactic obstacles that include conventional learning and reliance on a single textbook. Didactic obstacles play a central role in exacerbating the other two obstacles. This study concludes that learning design based on the GASING method has the potential to be an effective pedagogical alternative in reducing those learning obstacles.